An exploration of work-related stress and support structures experienced by occupational therapists working at a physical rehabilitation unit - Clarke, Jennifer (Stellenbosch : Stellenbosch University, 2016)
ENGLISH ABSTRACT: Introduction: Work-related stress is experienced in most working environments but can be particularly high in health-care environments. Support structures can help to alleviate the burden of work-related stress, but whether or not these structures are in place and adequate needs exploration. Aim: To explore and describe the work-related stress experienced by occupational therapists working at a physical rehabilitation unit and to determine whether the current support structures are addressing the work-related stress that they experience. Methods: This study was qualitative in nature. A phenomenological approach was used. Seven occupational therapists employed at the study setting were interviewed using semi-structured methods. Data was collected, transcribed and analysed by the researcher, and themes and sub-themes were extracted. Findings: All of the participants were experiencing quite high levels of work-related stress, mainly due to the nature of the work environment and challenges related to management and supervision. Other causes of stress were problems related to caseload, the role of the occupational therapist (OT) in the team, issues related to their colleagues and qualitative versus quantitative care delivery. The study also revealed that the participants were not satisfied with the support structures that were in place and had recommendations as to how the support structures could be improved to reduce work-related stress. Conclusion: The findings of the study confirmed the need for more effective support structures. Participants were quite vocal about the amount of stress and the lack of support they were experiencing – to the extent that they had to find alternative means of support. It was felt that management should show more awareness through acknowledging the therapists’ experiences, and that the organisation should put better support structures in place. Recommendations: Individual counselling, team building and group therapy sessions were recommended, as was decreasing the extent of responsibilities over-and-above the core job requirements or having smaller caseloads or more staff. Stellenbosch University https://scholar.sun.ac.za iv Among the many suggestions regarding managerial improvements were that managers should be more aware of the staff, help with the patients and be more empathetic. Improved communications through all levels of the Centre and a more representative measure of performance was also suggested.